Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1972
DOI: 10.19182/remvt.7816
|View full text |Cite
|
Sign up to set email alerts
|

Engraissement intensif de zébus Peulh sénégalais (Gobra). Quatrième partie : embouche en région rizicole. Males entiers ou castrés poids moyen 250 kg

Abstract: Rev. Elev. Méd. vét. Pays trop., 1972, 25 (1): 85-96

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The tendency was observed for 1 year old animals (average weight for males 144 kg and 129 kg for females) and 3 years old (364.30 kg for males and 309.50 kg for females). Valenza et al (1971a;1971b;1971c) and Calvet et al (1972) showed that intensive fattening of zebu Gobra during 4 months with local crop residues increased quantity and quality of meat. Furthermore, the study of on exteriorization of genetic potential of Gobra zebu confirmed the importance of feeding management.…”
Section: Discussion:-mentioning
confidence: 99%
“…The tendency was observed for 1 year old animals (average weight for males 144 kg and 129 kg for females) and 3 years old (364.30 kg for males and 309.50 kg for females). Valenza et al (1971a;1971b;1971c) and Calvet et al (1972) showed that intensive fattening of zebu Gobra during 4 months with local crop residues increased quantity and quality of meat. Furthermore, the study of on exteriorization of genetic potential of Gobra zebu confirmed the importance of feeding management.…”
Section: Discussion:-mentioning
confidence: 99%